Cryptocurrencies on the Eeu Market - Grigorevich Perepelitsa, Denis; AleÑ…androvich Galanov, Vladimir; Vladimirovna Galanova, AleÑ…andra; Badalov, Ashkhanovich; Aleksandrovich Markov, Maksim (International Journal of Engineering and Technology, 2018)
Modern financial technologies, in particular cryptocurrencies, penetrate deeper and deeper into the life of the modern world and the Russian society. The spread of cryptocurrencies in almost all areas is promoted by the following advantages: anonymity of payments, low commissions, and the inability to restrict the ownersâ€™ access to their funds. The use of cryptocurrencies is not limited to the banking and medical areas, insurance and services industries. Some experts suggest the creation of cryptocurrency as the single currency of the Eurasian Economic Union. Today this issue is only being discussed, but the advantages and a wide spread of cryptocurrencies prove that they can become one of the possible solutions in the currency agreement of the EEU being developed. To assess the prospects of using cryptocurrencies in the Eurasian Economic Union, it is necessary to analyze the prerequisites of cryptosystems, as well as to study the history of their development. The purpose of this article is to make a comparative analysis of cryptocurrencies on the EEU market in terms of possible use of the cryptocurrency as a supranational means of payment. The article considers the prerequisites of cryptocurrencies. Features of the currently most popular cryptocurrencies are analyzed. Possibilities of using them as EEU supranational payment means are estimated. Directions of the cryptocurrencies development on the EEU market are studied.Â Â